The diversity of Nepenthes at the post-mining area in Sintang District, West Kalimantan, Indonesia - HENDRA SETIAWAN; HILDA AQUA KUSUMA WARDHANI; KAMALUDIN KAMALUDIN; RIA ROSDIANA HUTAGAOL; RACHMI AFRIANI (Society for Indonesian Biodiversity, 2018)
Setiawan H, Wardhani HAK, Kamaludin, Hutagaol RR, Afriani R. 2018. The diversity of Nepenthes at the post-mining area in Sintang District, West Kalimantan, Indonesia. Biodiversitas 19: 1820-1827. Nepenthe is a tropical pitcher plant found in Indonesian archipelago and lives in nutrient leak habitat. One of Nepenthes nutrient leak habitat commonly found in Kalimantan Island is the post-mining area. This research aimed to know the habitat condition, species composition, species richness and diversity index of Nepenthes in Post-mining area in Sintang District, West Kalimantan Province. Thirty plots, each measuring 5 x 5-meter square, were established to survey the Nepenthes diversity in five locations of the post-mining area in Sintang District. There were 910 individuals of Nepenthes found spreading in two sub-Districts and five areas. Habitat condition in the post-mining area tended to be high in light intensity and temperature but low in humidity. Five Nepenthes species were found, namely N. ampullaria, N. bicalcarata, N. gracilis, N. mirabilis, and N. rafflesiana. Four natural hybrids were also found including N. xhookeriana, N. xkuchingensis, N. xneglecta, and N. xtrichocarpa. The species richness in post-mining area were 1.25 in Danau BTN (Bank Tabungan Negara/State Savings Bank) 0.95 in Dusun Kerangas, 0.58 in Sungai Ana Village, 0.21 in Jerora 1 and 0.20 in Danau Baning. The diversity index in Danau BTN, Dusun Kerangas, Sungai Ana, Jerora 1 and Danau Banning area were of low levels, respectively, 1.66, 1.3, 1.0, 0.64, and 0.68. Cluster analysis of species richness, diversity index, and abiotic factors showed that Danau Baning-Sungai Ana-Jerora 1 was grouped in the same cluster while Danau BTN and Dusun Kerangas were in a separate cluster.